Acoustical and mechanical properties of thermoplastic composites from discarded carpets. (15th August 2016) - Pan, Gangwei; Zhao, Yi; Xu, Helan; Ma, Bomou; Yang, Yiqi
Abstract: Without additional matrix or reinforcement, compression molded composites from waste polypropylene (PP) carpets/nylon (PA) carpets or PP carpets/polyester (PET) carpets have higher mechanical properties and sound absorption than traditional jute/PP composites. Large amount of carpets have been discarded every year, leading to waste of petro-based materials and serious environmental pollution. Fabrication of composites from discarded carpets via compression molding could save petroleum resources and alleviate environmental pressure. In this research, the compression molded composites from waste PP/PA carpets or PP/PET carpets showed good mechanical properties, sound absorption and water stability. Compared to the jute/PP composites, nylon 6, 6 (PA66)/PP carpet composites had 37% and 9% higher flexural strength and impact resistance, as well as 45% and 10% higher sound absorption and water stability, indicating their potential for transportation and construction industries.